Enhancing Islamic financial inclusion in Indonesia: Innovative strategies for rural and eastern regions - Said, Muhammad; Putra, Arya Nirwansyah Dwi; Tahir, Muhammad; Selfiani, Selfiani; Madi, Abdullah Habar (Priviet Social Sciences Journal, 2025)
This study aims to enhance Islamic financial inclusion in rural and eastern regions of Indonesia through innovative strategies, focusing on challenges related to access, literacy, infrastructure, and public trust issues. Using a qualitative library-based approach, this study analyzes literature from indexed journals, reports from the Financial Services Authority (OJK), and government policies published between 2018 and 2025. Data collection involves systematic literature searches using keywords such as “Islamic financial inclusion” and “Islamic fintech.” Content analysis is employed to identify patterns, challenges, and formulate strategies, with source triangulation to ensure validity. Research Findings Islamic financial inclusion in Indonesia stands at only 12.88%, significantly lower than the national inclusion rate (75.02%), due to limited access in rural areas (68.49%), low Islamic financial literacy (39.11%), geographic barriers, inadequate infrastructure, and product mismatches. Innovative strategies include: (1) contextual financial products such as musyarakah-based financing, (2) infrastructure strengthening through Islamic rural banks (BPRS) and digitalization, (3) financial literacy education, and (4) community-based awareness campaigns. Islamic fintechs (e.g., Alami, Ammana) show potential to overcome geographic constraints, though they are hindered by limited Internet penetration (60%) and digital literacy. These innovative strategies offer practical guidance for stakeholders to boost Islamic financial inclusion through contextual products, digitalization, community-based education, and women’s empowerment via MSMEs, supporting poverty alleviation and inclusive economic growth.